Vacunas SARS-CoV-2 - Bretón I, Andrea; Afani S, Alejandro (Revista Hospital Clínico Universidad de Chile, 2021)
Vaccines are biological products that stimulate the immune system to generate specific responses and immune memory. Faced with the magnitude of the problem caused by the Covid-19 pandemic, there is an urgent need to find an effective and safe preventive intervention. The race to find the ideal vaccine against this new coronavirus has required optimizing research times on this topic. Currently, more than 200 SARS-CoV-2 vaccine candidates are in development, 177 in preclinical evaluation, 63 in clinical evaluation and 16 of them in phase 3 of clinical trials. In our country, 3 SARS-CoV-2 vaccines are already authorized for administration, which have demonstrated safety and efficacy in clinical trials.